Remote Ischemic Conditioning Alters Methylation and Expression of Cell Cycle Genes in Aneurysmal Subarachnoid Hemorrhage. Issue 9 (September 2015) - Nikkola, Elina; Laiwalla, Azim; Ko, Arthur; Alvarez, Marcus; Connolly, Mark; Ooi, Yinn Cher; Hsu, William; Bui, Alex; Pajukanta, Päivi; Gonzalez, Nestor R.
Abstract : Background and Purpose—: Remote ischemic conditioning (RIC) is a phenomenon in which short periods of nonfatal ischemia in 1 tissue confers protection to distant tissues. Here we performed a longitudinal human pilot study in patients with aneurysmal subarachnoid hemorrhage undergoing RIC by limb ischemia to compare changes in DNA methylation and transcriptome profiles before and after RIC. Methods—: Thirteen patients underwent 4 RIC sessions over 2 to 12 days after rupture of an intracranial aneurysm. We analyzed whole blood transcriptomes using RNA sequencing and genome-wide DNA methylomes using reduced representation bisulfite sequencing, both before and after RIC. We tested differential expression and differential methylation using an intraindividual paired study design and then overlapped the differential expression and differential methylation results for analyses of functional categories and protein–protein interactions. Results—: We observed 164 differential expression genes and 3493 differential methylation CpG sites after RIC, of which 204 CpG sites overlapped with 103 genes, enriched for pathways of cell cycle ( P <3.8×10 −4 ) and inflammatory responses ( P <1.4×10 −4 ). The cell cycle pathway genes form a significant protein–protein interaction network of tightly coexpressed genes ( P <0.00001). Conclusions—: Gene expression and DNA methylation changes in aneurysmal subarachnoid hemorrhage patients undergoing RIC are involved in coordinated cell cycle and inflammatory responses. Abstract : Supplemental Digital Content is available in the text.